A historiografia da escravidão nos materiais didáticos de história do ensino médio do sistema estruturado de ensino do estado de Mato Grosso - Lopes, André Filipe Gonçalves (2023)
The present work has as its theme the historiography of slavery in the History teaching materials of the High School of the Structured Teaching System of the State of Mato Grosso. Based on the problem of trying to uncover which historiographical perspectives on black slavery are present in the teaching materials of the Structured Teaching System of Mato Grosso, the main objective will be to understand which historiographical perspectives are present in the structured material implemented by the State Department of Education - SEDUC/MT. In December 2021, SEDUC/MT announced the implementation of a Structured Teaching System, which includes printed and digital teaching materials produced by Fundação Getúlio Vargas - FGV together with Rede Maxi de Ensino, which will serve as sources in this dissertation. With the discourse that the state schools would be receiving the same teaching system used in private networks, the Mato Grosso government intends to invest R$549 million over two years through the Mais MT Program for the acquisition of the teaching system. In view of the implementation of the Structured Teaching System, schools will start receiving in 2022 the so-called "Structured Materials" to work with students. These materials are not subject to evaluation by the National Program of Books and Teaching Materials - PNLD. In view of the above, the specific objectives will be: 1) To analyze the form of the structured high school history materials implemented by SEDUC/MT; 2) To identify the history contents proposed by the material for high school; 3) To investigate the historiographic perspectives about slavery and race relations in Brazil presented by the material.